Identification and Heme Polymerization Inhibition Activity (HPIA) Assay of Ethanolic Extract and Fraction of Temu Mangga (Curcuma mangga Val.) Rhizome - Dhina Fitriastuti; Tatang Shabur Julianto; Annisa Wahyu Nur Iman (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Curcuma mangga Val. is one of Indonesian herbs from Zingiberaceae family that is under explored and could contain potentially active substances to serve as an antimalarial. This research intends not only to examine the antimalarial activity by means of heme polymerization inhibitor mechanism by using the ethanolic extract and fraction of Curcuma mangga Val. but also to identify its compound classification. The extract of temu manga was obtained by Soxhlet extraction method using ethanol solvent followed by fractionation using Vacuum Liquid Chromatography with solvent sequence n-hexane, n-hexane: ethyl acetate (2:1), ethyl acetate and ethanol. The extract and fraction were analyzed by using LC-MS and GC-MS. Activities of hem polymerization inhibition showed by IC50 values which were obtained from analysis of relationship between concentration sample and the percentage of inhibition using the PROBIT on statistical software. The result of HPIA assay shows that the IC50 value of ethanolic extract and ethanolic fraction of Curcuma mangga Val. rhizome are 2.273 and 1.479 mg/mL, respectively. It clearly shows that the heme polymerization inhibition activity of ethanolic fraction relatively better than that of ethanolic extract. Phytochemical screening determines the ethanolic extract contains saponin, terpenoid, and phenol while the ethanolic fraction contains terpenoid. Thus, terpenoid compound is presumed to be the inhibitor of heme polymerization. The results of analysis with LC-MS and GC-MS showed that the active compounds suspected to inhibit heme polymerization in ethanolic extract and fraction were (E) -labda-8 (17), 12-dien-15,16-dial and di-n-octyl phthalate, respectively. Keywords: antimalarial, Curcuma mangga Val., heme polymerization